Pendidikan Karakter dalam Membangun Generasi Berintegrasi dan Beretika - Cut Kumala Sari; Seri Pitri; Shafina Shafina (Asosiasi Riset Ilmu Pendidikan Indonesia, 2025)
Character education is essential to create a generation that is not only cognitively intelligent, but also strong in moral and ethical values. Amidst the rapid advancement of technology and globalization, maintaining the morality and integrity of the younger generation is increasingly difficult. By conducting literature research on 20 relevant sources, this article aims to investigate the role of character education in the formation of moral and ethical individuals. The results of the study indicate that character education that is included in the learning process, both formal and non-formal, is able to instill the values ​​of discipline, empathy, honesty, and responsibility. Strengthening character values ​​in the digital era also requires an approach that is in accordance with the culture and digital media that are close to students' lives. The implementation of consistent, collaborative, and contextual character education is the key to creating a generation that is not only academically superior, but also able to instill ethics in community life. Thus, character education is an important foundation in building the next generation of the nation with integrity and ethics.